E-004 Endovascular Embolisation of Spinal Perimedullary (Type IV) Fistula Using Ethylene Vinyl Alcohol Copolymer (Onyx): Is It Safe in Children?. (14th July 2013) - Honarmand, A; Soltanolkotabi, M; Ansari, S; Schoeneman, S; Patel, B; Hurley, M; Tomita, T; Shaibani, A
Abstract : Purpose: Several endovascular embolic agents have been utilised for permanent obliteration of perimedullary spinal arteriovenous fistulas (sAVFs) in children; however, endovascular embolisation using ethylene vinyl alcohol copolymer (Onyx) has not been widely described in treatment of this type of spinal lesion in children. We describe the usefulness of Onyx in endovascular embolisation of paediatric high-flow perimedullary sAVFs. Case Report: Case 1: During evaluation of a 7-year-old boy presenting with abdominal pain, incidental intraspinal vascular abnormalities were detected on a contrast-enhanced CT abdomen/pelvis study. Subsequent MRI revealed dilated vascular flow voids predominantly along the ventral surface of the spinal cord extending from the lower thoracic level to the cauda equina appearing to be intradural but extramedullary and suggestive of a perimedullary sAVF. The patient had been completely asymptomatic. Physical examination was normal except for an audible bruit in the lower back by auscultation. Case 2: A 17-year-old boy with a history of a cervico-spinal arteriovenous malformation presented with right lower extremity pain and progressive ambulatory disturbance. On physical examination he was noted to have considerable right lower extremity weakness associated with sensory deficits (mRS score: 4). Imaging Findings: Case 1: Spinal digital subtraction angiography (DSA) demonstrated a high flow intradural AVF at the L3–4 level supplying from an extremely hypertrophied anterior spinal artery arising from the left T9 intercostal, classified as perimedullary AVF (subtype B). Using detachable platinum coils and Onyx 18, progressive embolisation of the fistula was initiated in the efferent recipient vein with embolic reflux proximally across the fistulous site and into the distal afferent components of the three major feeding arteries for obliteration. Postembolisation spinal DSA one week later revealed a second separate perimedullary AVF subtype A supplied by the PSA which was resected surgically due to the small calibre of the posterior spinal artery supplying this AVF. Case 2: Spinal DSA demonstrated a high-flow dorsal perimedullary sAVF (subtype C) at C7-T1 level with a large recipient venous varix invaginating into the substance of the cervical cord posteriorly. The lesion was supplied from the PSA and the recipient varix drained superiorly into the dorsal longitudinal spinal veins exiting via the petrosal veins, superior petrosal sinuses, and sigmoid sinuses respectively. Embolisation of the AVF was performed utilising Onyx 34 to occlude the proximal venous efferent, with controlled reflux into the fistulous site and distal afferent of several arterial feeders. The patient achieved significant clinical improvement after one year (mRS score: 2). Conclusion: Although the safety of Onyx in individuals less than 18 years of age has not been yet well established, our initial results in a study on various types of CNS vascular malformations demonstrated that Onyx embolisation could be performed with high degree of safety and efficacy in children. To the best of our knowledge, use of Onyx in perimedullary sAVF embolisation in the paediatric population has been reported in only 3 cases. We believe Onyx embolisation could be performed with high degree of safety and efficacy in treatment of spinal perimedullary AVFs in children. Disclosures: A. Honarmand: None. M. Soltanolkotabi: None. S. Ansari: None. S. Schoeneman: None. B. Patel: None. M. Hurley: None. T. Tomita: None. A. Shaibani: None.